(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Ensuring the unity of measurements and the subject of étalones are very important in science, technology and everyday life. Through measurements, humans try to understand, research, and manipulate the world around them. Therefore, measurements need to be accurate, reliable and universal. This is done by ensuring the unit of measurements and by Etalons.